Strategi Pengelolaan Kampung Betawi Setu Babakan Sebagai Daya Tarik Wisata Di Jakarta Selatan - Hayati, Nurul; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 7 No 1 (2019): VOL 7, NO 1 (2019): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2019.v07.i01.p16, 2019)
Tourist Attractions in Indonesia can be found in the form of natural, art and cultural traditions. They can also be developed and utilized for sustainable tourism development. This culture tourism needs to be developed with the aim of preserving the culture itself. The aim of the organization is to preserve culture which is can be achieved effectively and efficiently by implementing a good management system. A good management can be improved if the components are well functioned. A good management has managerial functions, namely planning, organizing, directing and supervising. This research was conducted at the Setu Babakan Betawi Cultural Village,because it is the only tourist village that still exists in Jakarta that develops the concept of cultural tourism.This research uses observation, interview and documentation techniques. The informants were the staff of the Setu Babakan Betawi Cultural Village consists of service and information and administrative sub-section employees. The results of the study show that the management in the Betawi Cultural Village has already been conducted optimally, however there are still some inhibiting factors felt at the Setu Babakan such as structural and operational obstacles. In this study it is also discuss SWOT analysis. The strategies have been formulated such as using a land as an integrated tourist area, adding tourist attractions, preventing environmental pollution, and conduct counseling on the preservation of Betawi culture. Key words: cultural tourism, management functions, inhibiting factors, Betawi Village Setu Babakan.